2021
DOI: 10.5171/2021.119430
|View full text |Cite
|
Sign up to set email alerts
|

Measuring The Quality of Financial Statements After the Conversion To IFRS, Case of Poland

Abstract: Financial reporting around the world tends toward harmonization. The output of this process is increasing the number of countries that decided to transfer their accounting framework into IFRS. This paper encompasses the study on how the conversion to IFRS has affected the quality of financial statements in Poland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The table shows that in the analysed speciality literature the findings differ regarding the impact of the IFRS standards. Many authors have expected to observe a significant impact, yet the results have shown that this has been a minimal one (Piechocka-Kaluzna, 2021;Napier & Stadler, 2020;Tomi, 2018). On the other hand, some authors claim that the implementation of the IFRS standards combined with the rapid transition to them may bring huge benefits to countries with emerging economies (Akisik, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The table shows that in the analysed speciality literature the findings differ regarding the impact of the IFRS standards. Many authors have expected to observe a significant impact, yet the results have shown that this has been a minimal one (Piechocka-Kaluzna, 2021;Napier & Stadler, 2020;Tomi, 2018). On the other hand, some authors claim that the implementation of the IFRS standards combined with the rapid transition to them may bring huge benefits to countries with emerging economies (Akisik, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%